1991
DOI: 10.1346/ccmn.1991.0390203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Na-Hexametaphosphate on the Hydraulic Conductivity of Kaolinite-Sand Mixtures

Abstract: Abstract--Mixtures of kaolinite clay and quartz sand were packed in columns and leached with NaCICaC12 solutions of different concentrations (ranging from 0.5 M to distilled water) having sodium adsorption ratios (SAR) of 5, 10 and 20. Sodium hexametaphosphate (NaHMP) (10 g/m s) was added to each solution. Changes in the hydraulic conductivity (HC) and clay concentration in the effluent were measured, and the dispersion of the clay was evaluated. In the absence of NaHMP, using distilled water instead of 0.01 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Moreover, ultrasound dispersion generates more <1 µm particles, while chemical dispersion yields more >1 µm particles. The chemical dispersant, NaHMP, may alter the particle sizes in two ways: (1) it can partly reverse the clay mineral's positive edge charges by (PO 3 -) 6 and hence reduce the tendency of aggregation via edge-face interactions (Levy et al, 1991) and (2) the added Na + can exchange with the interlayer Ca 2+ , resulting in a change of Ca 2+ -Mt to Na + -Mt that can swell further and then exfoliate into smaller particles (as discussed previously). Therefore, adding the dispersant, NaHMP, to Ca 2+ -Mt may generate misleading PSD results because of the partial conversion of Ca 2+ -Mt to Na + -Mt.…”
Section: Ca 2+ -Mtmentioning
confidence: 99%
“…Moreover, ultrasound dispersion generates more <1 µm particles, while chemical dispersion yields more >1 µm particles. The chemical dispersant, NaHMP, may alter the particle sizes in two ways: (1) it can partly reverse the clay mineral's positive edge charges by (PO 3 -) 6 and hence reduce the tendency of aggregation via edge-face interactions (Levy et al, 1991) and (2) the added Na + can exchange with the interlayer Ca 2+ , resulting in a change of Ca 2+ -Mt to Na + -Mt that can swell further and then exfoliate into smaller particles (as discussed previously). Therefore, adding the dispersant, NaHMP, to Ca 2+ -Mt may generate misleading PSD results because of the partial conversion of Ca 2+ -Mt to Na + -Mt.…”
Section: Ca 2+ -Mtmentioning
confidence: 99%
“…Frenkel et al (1992) showed that addition of small amounts of the anions to suspensions containing reference clays increased the critical flocculation concentration (CFC) of Na-montmoriUonite five to six times, and that of Na-kaolinite by an order of mag-515 nitude. Levy et al (1991) added a very small amount (10 g m -3) of hexametaphosphate to a kaolinite-sand mixture and noted that it caused a sharp decrease in the kaolinite's HC.…”
Section: Introductionmentioning
confidence: 99%